PROSES INTERNASIONALISASI PT. INDOFOOD DALAM BERINVESTASI DI NIGERIA MELALUI FOREIGN DIRECT INVESTMENT - Nurdiana Abhiyoga; Maulida Zuiyina Hamida; Bellinda Calvina; Fadel Rizky Attala (Dauliyah Journal of Islamic and International Affairs, 2021)
This research will discuss about internationalization process from PT. Indofood Sukses Makmur Tbk in Nigeria. In the process, PT Indofood conducted a Joint Venture with the Salim Group, Indonesia (the center company of PT. Indofood Sukses Makmur) with the Tolaram Group (Singapore). As a Multi National Corporation (MNC), PT. Indofood has succeeded in increasing the company’s presence into the international realm and can be accepted by Nigeria. PT. Indofood Sukses Makmur Tbk with its Foreign Direct Investment (FDI) strategy with other multinational companies. It will also help the company to grow optimally in the local and international markets. Therefore the authors will try to analyse the strategies used by PT. Indofood Sukses Makmur using qualitative methods and secondary data, such as previous journals and reports issued by the company.